2021
DOI: 10.1111/jfr3.12694
|View full text |Cite
|
Sign up to set email alerts
|

How do people perceive flood risk? Findings from a public survey in Tuscany, Italy

Abstract: The study of risk perception (RP) has much increased in the last years to improve flood risk management. Effective communication requires an understanding of how the risk of flooding is perceived by residents of different areas. In this work, RP is investigated through a survey involving 483 people living in Tuscany. RP was assessed through a score built on four items covering personal, residence, and sociodemographic variables concerning flood RP. Results showed that: (a) flood RP was moderate; (b) RP was pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…[49] explored appropriate flood-related urban planning using a qualitative approach in five steps and surveyed to investigate perceived risk (RP). RP was assessed through a score built on four items covering personal, residence, and sociodemographic variables related to RP flooding [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[49] explored appropriate flood-related urban planning using a qualitative approach in five steps and surveyed to investigate perceived risk (RP). RP was assessed through a score built on four items covering personal, residence, and sociodemographic variables related to RP flooding [50].…”
Section: Resultsmentioning
confidence: 99%
“…In this work, Risk Perception (RP) is investigated through a survey involving 483 people living in Tuscany. RP was assessed through a score built on four items covering personal, residence, and sociodemographic variables related to RP flooding [50].…”
Section: No Authormentioning
confidence: 99%
“…However, the increasing uncertainty on future socio-economic developments (that affect mean sea level) and anthropogenic activities within estuaries (that affect estuarine geomorphology) makes more complex and uncertain to accurately predict the future inundation extent, posing major challenges to the efficient and sustainable management of estuaries. Moreover, as flood mapping directly influences flood risk perception and public awareness, engagement and preparedness 28 , 30 , care must be taken when communicating flood projections and underlaying uncertainties since this influences trust in science and message acceptance 56 , 57 . In detail, the previous studies concluded that including uncertainty information in climate change promotes public trust in climate science, since a range of possible futures may be seen as more credible than a single, worst-case scenario.…”
Section: Discussionmentioning
confidence: 99%
“…frequency and duration of flood events, the existence of flood barriers, likely scenarios, etc.). Considering that flood mapping and flood communication directly influences flood risk perception 28 30 , it is fundamental to deliver reliable high resolution flood maps and support the translation of the scientific projections and data to the public. Otherwise, the disclosure of exaggerated projections has counterproductive effects, as it discredits the results of science and demobilizes the public about the relevance of climate change, since, due to their knowledge of the local reality, they do not consider the scenarios presented as possible.…”
Section: Introductionmentioning
confidence: 99%
“…2) according to the common presence in the titles and abstracts, and we tried through the bibliographic search to know the possibility of the impact of these factors on the population of the city of Batna and understand the reasons for the failure to form a new community vision of the danger of flooding,A vision that clarifies the size of the expected threats, as a background to present suggestions and recommendations to mobilize community efforts as an important element in the preventing and handling flood risk in the future. (Burningham et al, 2008;Zabini et al, 2021)have attempted to understand the basis of awareness and its relationship to flood risk preparedness through their study of a population at risk.…”
Section: Methodsmentioning
confidence: 99%